2016
DOI: 10.1103/physrevb.93.064105
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy optical phonon modes in the caged compoundLaRu2Zn20

Abstract: The caged compound LaRu 2 Zn 20 exhibits a structural transition at T S =150 K, whose driving mechanism remains elusive. We have investigated atomic dynamics by the measurements of specific heat C and inelastic X-ray scattering (IXS). The lattice part of the specific heat C lat divided by

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…However, for LaRu 2 Zn 20 it was recently reported that the Zn ions at the 16c site exhibit low energy, localized vibration modes (rattling). [25] This is indicative of "loose" Zn ions at this site due to the presence of extra space and consequently broadened Madelung potentials. If so, the larger Cd atoms may be expected to occupy this site preferentially, and the small decrease in the value of Θ D is due to the greater atomic mass of Cd.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…However, for LaRu 2 Zn 20 it was recently reported that the Zn ions at the 16c site exhibit low energy, localized vibration modes (rattling). [25] This is indicative of "loose" Zn ions at this site due to the presence of extra space and consequently broadened Madelung potentials. If so, the larger Cd atoms may be expected to occupy this site preferentially, and the small decrease in the value of Θ D is due to the greater atomic mass of Cd.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The equivalent isotropic atomic displacement parameters of B eq of Al(16c) are characterized by one and half times larger than those of other atoms, which was observed in other RTr 2 X 20 compounds for X = Al [20,21] and X = Zn [22,23]. Note that RTr 2 X 20 compounds feature a cage structure that Al(16c) is located in the cage composed of two Yb(8a) atoms and twelve Al(96g) atoms.…”
Section: Resultsmentioning
confidence: 66%
“…The (red) solid curves are the fits to the C(T ) data for 50 < T < 300 K by adopting the Debye model for acoustic phonon modes [34] with the Debye temperatures of θ D = 312(1) K for R = Pr and 317(1) K for R = Nd. The values of θ D are higher than that of θ D = 259 K for an isostructural LaRu 2 Zn 20 [35], which is reasonable because the molecular weights of RNi 2 Mg 20 for R = Pr and Nd are much lighter than that of LaRu 2 Zn 20 . The insets display the C/T 3 plots with the logarithmical scale.…”
Section: Specific Heat and Magnetic Entropymentioning
confidence: 69%